Labyrinths and Illusions in David Lynch’s Mulholland Drive and Inland Empire - Ebrahim Barzegar (CINEJ Cinema Journal, 2016)
David Lynch is known for its surrealistic and bizarre spectacles in his films in and out of America which puzzle and disturb the viewers and yet force them to ponder on the underlying mystery and meaning of them. Multilayered and disjointed narratives of his films strike most of the viewers to get lost in his magical world or Lynchland. In order to fully apprehend his convoluted cinematic narrative, this article aims at unfolding the different layers of his postmodern award-winning film, Mulholland Drive (2001) and INLAND EMPIRE (2006). To achieve this goal, Brian McHale’s thoughts and notions associated with postmodern fiction’s characteristic dealing with foregrounding ontological narratives are chosen and used in this research. It is conclude that Mulholland Drive’s and INLAND EMPIRE's embedded narratives function as a reflection of the primary narrative or diegetic leading to the construction of abysmal worlds.